EFFECT OF CLOMIPHENE CITRATE ON SOME ASPECT OF REPRODUCTIVE SYSTEM IN MATURE FEMALE RABBITS - Ali, Maesem Hassan (Diyala Agricultural Sciences Journal, 2013)
The effect of clomiphene citrate on the hormones, ovary and endometrium were studied in mature female rabbits treated with 10mg/kg twice daily for 20 days. Results cleared that there were a significant (p<0.05) increase in the follicle stimulation hormone(FSH), estrogen and progesterone concentration , while, no significant changes were noticed in luteinizing (LH )and testosterone concentration . The most pronounced changes in reproductive system of female rabbits were found in the corpus lutium and filled with vacuolated cell, as well as endometrial hyperplasia occur. On the other hand gross section showed multi follicular (different numbers )on the right and left ovaries of female rabbits.